Designing a Chatbot Based on Full-Text Search and 3D Modelling as a Promotional Media - Ferdian, Sevtian; Hermawan, Aditiya; Edy, Edy (JUITA: Jurnal Informatika, 2023)
A chatbot is an application that can respond and reply to questions from the questioner, without any human being involved. In general, chatbots are used to simplify and improve public services, so that users can get information quickly and directly, without time constraints. This research objective is to create promotional media in the form of chatbots in the 3D Virtual Tour to answer questions and provide general information about an object while providing more attractive visuals for users. The method used to run the chatbot is Full-Text Search. Full-Text Search is an efficient and powerful search method that is built into MySQL by default, which works by matching words between keywords and patterns in the database. This study succeeded in applying the Full-Text Search method as a search technique for chatbot patterns in the 3D Virtual Tour application at Buddhi Dharma University as a promotional medium. Evaluation using the User Acceptance Test (UAT) method yielded a value of 83.45% in a very satisfying category for users.